The Green Innovative Power of Carbon Neutrality in China: A Perspective of Innovation Efficiency in China’s High-Tech Industry Based on Meta-Frontier DEA - Zou, Wenjie; Shi, Yi; Xu, Zhihao; Ouyang, Fang; Zhang, Lin; Chen, Huangxin (Frontiers in Environmental Science, 2022)
The high-tech industry plays a crucial role in reducing carbon emission and achieving green economic development. This research uses Meta-frontier DEA to measure the innovation efficiency level of the high-tech industry in China’s provinces from 1999 to 2018, compares the difference in this industry’s innovation efficiency under the regional frontier and common frontier, and inspects the convergence condition of its innovation efficiency in the three major areas of eastern, central, and western China. The results show under the regional frontier that the difference in innovation efficiency of the western region’s high-tech industry is the biggest, while the difference in the central region is the smallest, and under the national common frontier the innovation efficiency level of the eastern region’s high-tech industry is the highest, while that of the western region is the lowest. The regional pattern of innovation efficiency in the high-tech industry is consistent with the development trend of the regional economy. Moreover, by using the ratio of the technology gap ratio, we find that the eastern region has the potential optimal technology in China, whereas the central and western regions have large room for improvement. Lastly, the stochastic convergence test shows that the innovation efficiency of the central region’s high-tech industry presents a convergence trend, but the same trend does not occur in the western and eastern regions as well as for the whole country.